Implementation of CSR PT. Wika Beton, Tbk-Ppb Sumut in the Field of Education Through the “Wika Teaching” Program in SMK Negeri 2 Binjai - Idolla Adha Yanti; Badaruddin Badaruddin; Indra Fauzan (Budapest International Research and Critics University, 2022)
Social Responsibility or what we are better known as CSR today is an inseparable aspect of the company. Providing CSR assistance in the field of education with the